Bio‐Based Cycloalkanes: The Missing Link to High‐Performance Sustainable Jet Fuels. Issue 22 (4th November 2020) - Muldoon, Jake A.; Harvey, Benjamin G.
Abstract: Invited for this month′s cover is the group of Ben Harvey at the Naval Air Warfare Center, Weapons Division, China Lake. The image shows several examples of bio‐based cycloalkanes that have been developed as next‐generation sustainable jet fuels. The Review itself is available at 10.1002/cssc.202001641 . Abstract : "Advanced biofuels can actually outperform petroleum‐derived fuels…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202001641 . View the Front Cover here: 10.1002/cssc.202002327 .